Da licenciatura ao início da docência: vivências de professores de matemática na utilização das tecnologias da informação e comunicação - Carneiro, Reginaldo Fernando (Universidade Federal de São Carlos, 2008)
This research aims to investigate the contributions of UFSCar s Teaching License in Mathematics and the experiences of teachers at the beginning of their careers when introducing and using the Information and Communication Technology ICT in their classes. This is a qualitative-based study which consisted of three different moments: in the first one, I used a questionnaire to try to identify the graduates who were working as teachers and using any technology in their practices. In the second moment, teachers who said they use some kind of technology answered another questionnaire in order to provide information about the contributions of initial education regarding the use of ICT. Finally, in the last moment, four teachers were selected for the semi-structured interviews so that I could identify their experiences at the beginning of their careers in the introduction and use of technologies. During the analysis, I made a first attempt to organize the data in tables for an easier viewing of all the answers. Then I did a more systematic analysis of this data, making inferences, forming hypotheses and getting in contact with the literature of the area. This process resulted in three categories of analysis: (1) the contributions of initial education for the use of Information and Communication Technology, (2) the characteristics of the survival and (3) the characteristics of the discovery. Within the categories on the characteristics of survival and discovery, I was able to identify the particular aspects of the beginning of career and also some others that have arisen when teachers made use of technologies. The discussion of the results showed that the teaching license in mathematics from UFSCar provided the contact of the graduates with environments of discussion and reflection on the use of ICT, enabling them to become self-directed to seek new ways to teach the mathematical content. Even tough the initial education had dealt with this issue, many dilemmas and challenges were identified in the teachers experiences, what demonstrates the complexity that permeates this practice. Besides the difficulties, questions, fears, anxieties and insecurities, frequent in the beginning of career to maintain discipline in the classroom, to motivate the students, to complete the program, the fear of failing to teach and to start giving a class when the school year is already under way highlighted by national and international literature on this subject, others are due to the increased use of such tools, such as: insufficient number of equipment, a large number of students per class, lack of maintenance of computers, laboratories with inappropriate structure to receive a large number of students, students lack of knowledge regarding the technologies, specific softwares to teach mathematics not installed in the computers and fear because of the unpredictability of these classes. However, the various ways in which the technologies were used showed great creativity and clarity of objectives, and the positive experiences that were at that stage may have contributed to minimize the shock of reality and, moreover, other experiences such as participation in continuing education courses and support of collaborative groups may have helped in the stage of professional development.
Keywords: Educação e licenciatura; Professores iniciantes; Tecnologias da informação e comunicação; Licenciatura em matemática; Início de carreira docente; Teaching license in mathematics; Beginning of a teacher career; Information and communication technology; CIENCIAS HUMANAS::EDUCACAO